Analisis Sentimen Publik Terhadap Transparansi Laporan Keuangan Lembaga Zakat di Media Sosial: Studi Kasus Menggunakan Brand24 - Karimah, Nilna Arzaq (Tuturlogi: Journal of Southeast Asian Communication, 2025)
This study investigates public sentiment toward the transparency of financial reporting by zakat management institutions in Indonesia, with a focus on how these perceptions manifest on social media platforms. Despite the high potential of zakat in Indonesia, public trust in its management remains fragile, often due to a lack of transparency. Using a netnographic qualitative approach, this research employs Brand24 a social media monitoring tool to collect and analyze digital convertations related to the financial transparency of organizations such as BAZNAS and Rumah Zakat between April 19 and May 19, 2025. The fidings reveal a significant fluctuation in both positive and negative sentiments over the observation period, indicating public secsitivity to issues of transparency. The fifth week of monitoring recorded the highest level of positive sentiment, while the fourth week saw a spike in criticism. Mentions and reach analyses show that social media, particularly Twitter, Tik Tok, and online news, play a pivotal role in shaping public discourse. This research concludes that media sentiment is a critical indicator of public trust and highlights the need for zakat institutions to improve transparency through proactive digital communications strategies. The study contributes to understanding the intersection of digital communications, Islamic philanthropy, and public accountability in the digital era.